Plain Truth : novel - Picoult, Jodi (London [u.a.] : Hodder Dargaud, 2000)
The discovery of a dead infant in an Amish barn shakes Lancaster County to its core. But the police investigation leads to a more shocking disclosure: circumstantial evidence suggests that that eighteen-year-old Katie Fisher, an unmarried Amish woman believed to be the newborn's mother, took the child's life. When Ellie Hathaway, a disillusioned bigcity attorney, comes to Paradise, Pennsylvania, to defend Katie, two cultures collide - and, for the first time i her high profile career, Ellie faces a system of justice very different from her own. Delving deep into the world of those who live 'plain', Ellie must find a way to reach Ellie on her terms. As she unravels a tangled murder case, Ellie also looks deep within - to confront her own fears and desires when a man from her past comes back into her life.